[A03] Limb Occlusion after Endovascular Abdominal Aortic Aneurysm Repair. (November 2022) - Basra, Melvinder; Hussain, Purvez; Ho, Sebastian; Li, Mimi; Kulkarni, Shreya; Armon, Matthew; Choksy, Sohail
Abstract : Objective: Limb occlusion is a potentially serious consequence of endovascular abdominal aortic aneurysm repair (EVAR). This case–control study identifies predisposing factors. Methods: A consecutive series of patients from two centres undergoing EVAR from 2007 to 2017 were identified retrospectively. Patient record interrogation allowed collation of demographics, intra- and peri-operative data, and surveillance data. The pre-operative computed tomography angiography was analysed to determine EVAR relevant anatomical data. The primary outcome was occlusion of an EVAR limb. Results: A total of 787 patients (702 males; median age 78 years, range 53 – 94 years) were analysed. Fifty patients reached the primary outcome, resulting in an overall limb occlusion rate of 50/787 (6.35%). Factors predictive of limb occlusion were oversizing by > 10% of the native vessel diameter; oversizing of > 20%, 25/50 (50%) affected; external iliac artery landing zone, 12/50 (24%) affected; and post-operative kinking, 5/50 (10%) affected. Fifty randomly selected controls with similar baseline characteristics were studied. Oversizing of the iliac endograft was found to be significantly greater in the limb occlusion group than the controls. This difference was statistically significant according to the Mann–Whitney U test ( p < .05). Iliac tortuosity did not contribute to limb occlusion. Binomial logistic regression excluded statistically significant confounding. The Cook endograft had a 9% limb occlusion rate across sites. Medtronic and Vascutek endografts had 2.4% and 2.5% limb occlusion rates respectively. Conclusion: Oversizing of EVAR limbs by > 10% is a key factor contributing to limb occlusion and the Cook endograft appears more susceptible. Meticulous case planning with judicious oversizing has the potential to change practice.